The early anthropogenic hypothesis: A review. (15th July 2020) - Ruddiman, W.F.; He, F.; Vavrus, S.J.; Kutzbach, J.E.
Abstract: The 'early anthropogenic hypothesis' (EAH), published in 2003, proposed that early agricultural humans transformed planet Earth by adding CO2 to the atmosphere by deforestation after 7000 years ago and by adding CH4 to the atmosphere by wet-rice farming and livestock tending after 5000 years ago. Later work led to the insight that the resulting warming of the atmosphere and the ocean would have contributed additional CO2 feedback by reducing CO2 solubility in the global ocean and by boosting ventilation from the Antarctic Ocean surface due to suppressed Antarctic sea-ice extent. This paper summarizes new findings from multiple scientific disciplines that document how the steadily spreading human influence transformed their environment after 7000 years ago. We blend this new evidence into a revised version of the EAH, and we also evaluate proposed alternatives to the anthropogenic explanation. Highlights: The paper contains a summary of all major evidence supporting the early anthropogenic hypothesis. The paper contains an analysis of all other proposed explanations for the late Holocene CO2 rise. It summarizes the major factors that govern the late Holocene CO2 budget.